Spline Truncated Nonparametric Regression Modeling for Maternal Mortality Rate in East Java - Fadhlul Rahim; I Nyoman Budiantara; Erma Oktania Permatasari (Inferensi, 2019)
Maternal Mortality is the number of maternal deaths recorded during pregnancy, childbirth, and childbirth caused by pregnancy and childbirth, but not caused by accidents or falls. Since 2012 until 2015 it has been noted that maternal mortality rate has decreased from 359 to 305 maternal deaths per 100,000 live births. Despite the decline, the figure is still far from the target of the Sustainable Development Goals (SDGs) of 70 deaths per 100,000 live births. The analytical method used to determine the factors that influence maternal mortality rate is Nonparametric Spline Truncated Regression because the pattern of correlation between maternal mortality rate and each predictor variable obtained does not form a particular pattern. Based on the model obtained, the results are that all predictor variables have a significant effect on maternal mortality rate, namely the percentage of households with clean and healthy behavior, percentage of obstetric complications handling, percentage of pregnant women visits, percentage of households receiving cash assistance, and ratio of health centers and hospitals with a determination coefficient is 88 ,13 percent.